(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
The damage profile of GaAs substrate with the interaction of Silver (Ag) ions with energy of about 100 KeV changes the properties of a GaAs substrate related to its properties of the structure. Here, structural damage in GaAs substrate due to 100 KeV Silver ions interaction has been performed with SRIM/TRIM software regarding surface binding energy which is observed 2.82 eV for Ga and 1.26 for As, lattice binding energy is 3eV for both Ga as well as As and displacement energy is 25 eV. The work shows that the backscattered ions are observed 55, and vacancies per ion are 1102. The ion range is observed at 322 angstroms. Silver (Ag) Ions transfer a large amount of energy to the atomic lattice, which is responsible for the dislocation of the lattice atoms from their original positions. The damage profile has been studied as a function of dpa, which shows that the radial range is 144 angstroms for 100 Kev Silver(Ag) ions penetrations into the GaAs substrate.